Bilateral Approach with Botulinum Toxin Type A Injections in Patients with One-Sided Facial Hyperkinetic Movements - Karapantzou, Chrisanthi; Vale, Joao Pedro; Haubner, Frank Joachim; Zagoridis, Konstantinos; Agas, Konstantinos; Karagogos, Konstantinos; Zagoridou, Nikoleta; Canis, Martin (Archives of Clinical and Medical Case Reports, 2022)
Background: Main subject of our investigation was to clarify, if a bilateral approach with Botulinum toxin type A injections is more efficient from cosmetic and functional aspect, compared to unilateral injections, in patients with one-sided facial hyperkinetic movements, like synkinesis and hemi facial spasm. Methods: Our patient cohort included 30 patients suffering from unilateral hyperkinetic facial contractions. We performed a total of 60 injections, 30 of them only on the affected side and 30 on both facial sides. All participants underwent 2 botulinum toxin sessions, with a 4 months period lying between the injections. Our statistical analysis was divided into 4 hypothesis testing - sub-groups, based on the results of the subjective satisfaction rates our patients delivered 2 months and 6 months after the initial botulinum toxin session. Furthermore 2 doctors evaluated the results based on pre-and after photographs on a Quartile Grading Scale for objective evaluation for the same time periods. Each one of the observers received one patient group, either with bilateral or with ipsilateral treatments, without knowing which group they received. Results: Summarizing the statistical results we analyzed from both sources (patients and doc-tors-observers), we found statistically significant differences in satisfaction rate between the two groups (p=.004) and a better objective evaluation on patients who underwent combined treatments. Conclusions: Our work confirmed the initial assumption that patients with facial asymmetry of different etiology benefit from a bilateral therapeutic approach with botulinum toxin injections, instead of one-sided injections into the hyperkinetic or dyskinesia facial side.